Preparation of Standard Operating Procedures (SOPs) for Procurement of Goods, Especially Shopping for Consumables of Practical Materials at SMK Negeri 6 Batam - Cessy Yulia Nofia (MID Publisher International, 2023)
This final project discusses the mechanism of procurement of goods, especially the expenditure of consumables for practice at SMK Negeri 6 Batam, starting from submitting a budget plan to the process of spending on goods. The purpose of this study was to determine the causes of wasted spending, to find out the causes of incomplete supporting documents and to make Standard Operating Procedures (SOP) for procurement of goods. In this study, the authors used the method of data collection interviews, documentation and observation. For the data analysis method using descriptive data analysis method supported by qualitative data. Given this research requires exposure and analysis of events that occurred during the procurement process.